Minería para el buen vivir: Discursos sobre extractivismo y buen vivir en el Ecuador de la Revolución Ciudadana (2007-2017) - Jandik, Mirjana (Notas de Antropología de las Américas, 2025)
Buen vivir was a key dispositive of the administration of Rafael Correa (2007-2017)in Ecuador. Based on a critical discourse analysis, this article analyzes its inscriptionin the constitution and national development plans and shows how it has been usedby the government to legitimize neoextractivist practices.